Hypofractionated Concomitant Chemoradiation in Inoperable Locally Advanced Non-small Cell Lung Cancer: A Report on 100 Patients and a Systematic Review. Issue 2 (February 2019) - Iqbal, M.S.; Vashisht, G.; McMenemin, R.; Atherton, P.; McDonald, F.; Simmons, T.; Bradshaw, A.; Kovarik, J.; Turnbull, H.; Dodd, L.; Mulvenna, P.; Greystoke, A.
Abstract: Aims: Concomitant chemoradiation is the standard of care in patients with inoperable non-small cell lung cancer. The purpose of this study was to analyse the survival outcome and toxicity data of using hypofractionated chemoradiation. Materials and methods: One hundred patients were treated from June 2011 to November 2016. Treatment consisted of 55 Gy in 20 daily fractions concurrently with split-dose cisplatin vinorelbine chemotherapy over 4 weeks followed by two cycles of cisplatin vinorelbine only. Survival was estimated using Kaplan–Meier and Cox regression was carried out for known prognostic factors. A systematic search of literature was conducted using Medline, Embase and Cochrane databases and relevant references included. Results: In total, 97% of patients completed radiotherapy and 73% of patients completed all four cycles of chemotherapy. One patient died of a cardiac event during consolidative chemotherapy. There were two cases of grade 4 toxicities (one sepsis, one renal impairment). Grade 3 toxicities included nausea/vomiting (17%), oesophagitis (15%), infection with neutropenia (12%) and pneumonitis (4%). Clinical benefit was seen in 86%. Two-year progression-free survival and overall survival rates were 49% and 58%, respectively. The median progression-free survival and overall survival were 23.4 and 43.4 months, respectively. The only significant prognostic factor was the number of chemotherapy cycles received ( P = 0.02). The systematic review identified 13 relevant studies; a variety of regimens were assessed with variable reporting of outcomes and toxicity but with overall an improvement in survival over time. Conclusion: Our experience compared with the original phase II trial showed improved treatment completion rates and survival with acceptable morbidity. With appropriate patient selection this regimen is an effective treatment option for locally advanced non-small cell lung cancer. This study helps to benchmark efficacy and toxicity rates while considering the addition of new agents to hypofractionated concurrent chemoradiotherapy. The agreement of a standard regimen for assessment in future trials would be beneficial. Highlights: Largest series of real-life experience of using SOCCAR regimen in NSCLC. Two-year progression-free and overall survival were 49% and 58%, respectively. Median progression-free and overall survival were 23.4 and 43.4 months, respectively. Systematic review of hypofractionated concomitant chemoradiation in NSCLC identified 13 relevant studies. There has been an improvement in survival over time.